Effects of Apis Mellifera, Apis Cerana, and Trigona SP on 20 M Sprint Performance - K Kusnaedi; Mukti Priastomo; I Ketut Adyana; S Sukrasno (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
This study aimed to determine the effect of three types of honey from three different honey bee species on increasing stamina and anti-fatigue effect by examining their effects on the biochemical process in the anaerobic pathway. Tests were carried out on humans who had met the specified criteria. The method used in this study was an experimental method involving 30 healthy students. The inclusion requirements consisted of males aged 18-20 years, weight 50-70 kilograms, height 160-170 cm, normal momentary blood sugar levels 140 mg/dL, VO2max 35-40 ml/kg/min, normal blood pressure, and not having severe diseases such as diabetes, asthma, kidney failure, hepatitis, as well as other serious diseases that hinder physical activity. Volunteers had also filled out informed consent stating their willingness to participate in the research to completion. The results of this study showed that there was a change between pre and post in each groups, indicating that each honey content had a significant impact on improving the participant performance. In addition, this study found changes in the three types of honey (Apis Mellifera, Apis Cerana, Trigona SP) in the participant running performance improvement. However, there was no significant difference between the three types of honey.